Aboriginal Human Research Ethics Committees ensuring culturally appropriate research. (30th September 2020) - Finlay, S; Keed, V; Kelly, D; Cashman, M; Green, S
Abstract: Aboriginal and Torres Strait Islander people, Australia's Indigenous peoples, make up three percent of the population of Australia. Like many other Indigenous peoples in colonised countries, they suffer the worst health and social status of any population group. Australian Indigenous people have a lower life expectancy (8.6 years lower for men and 7.8 years for women) compared with other Australians (ABS 2018a). The reasons for the poorer health outcomes are complex and include historical, political and social factors (AIHW 2015a). The health disparity has driven a high number of research projects with a focus on Australian Indigenous people or mainstream research projects where Australian Indigenous people are overrepresented. Given the uniqueness of Australian Indigenous cultures as well as the historical, political and social context, in 1998, the Aboriginal Health and Medical Research Council of New South Wales (AH&MRC) established an Australian Indigenous-specific human research ethics committee (HREC). The AH&MRC is the Indigenous peak health body of New South Wales. This presentation will outline the role and benefit of the AH&MRC HREC as a specialised HREC. The AH&MRC HREC is fully constituted and registered under the National Health and Medical Research Council (NHMRC). The NHMRC is the leading expert body in health and medical research in Australia and develops health research guidelines. The AH&MRC HREC is one of three AHRECs in Australia. The AH&MRC Ethics Committee not only guarantees that research is conducted ethically but also ensures research involving Indigenous people is undertaken in a culturally appropriate manner. One of the key elements required by the AH&MRC is that researchers consult Indigenous communities across all stages of the project from the design, implementation, analysis and write up. The AH&MRC HREC is essential, ensuring the research is of benefit to the Indigenous community in NSW and is conducted in a culturally safe manner. Key messages: Specialised Indigenous human resarch ethics committees are vital to enuring research is culturally appropriate. Spscialised human resarch ethics committees can be of benefit for other disctinct populations.